ئاستە تەکنیکییەکانى(وەزیفییەکانى) ئاسایشى نەتەوەیى - الدین, واحد عمر محى (Sulaimani Journal for Humanities, 2003)
This research deals with the technical ( functional ) levels of national security. Moreover „from the standpoint that the researcher has adopted the modern (societal ) method of national security which relates it to development , we have outlined four main technical levels with peculiar implications and characteristic features. These two interacting together , will much highlight the level of national security of a state , the levels are the political and ideological, social economic and military security. It is important to note that the researcher has reached a number of conclusions, recommendations and suggestions including outlining the functional levels of national security in four main levels and the necessity of studying and understanding national security from the modern societal perspective , This is added to a state strategy based on this ground taking into consideration the peculiarities and priorities of each state and the necessity of understanding the decision-makers in the different states, the reality of the intimate relationship between national Security and the adoption of a pluralistic democratic ruling system.... etc.